2023
DOI: 10.1186/s12871-023-02014-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of dexmedetomidine as an adjuvant for high-thoracic erector spinae plane block for analgesia in shoulder arthroscopy; a randomized controlled study

Abstract: Background Management of postoperative pain after shoulder arthroscopy is an important issue. Dexmedetomidine, as an adjuvant, improves nerve block efficacy and decreases postoperative consumption of opioids. As a result, we designed this study to determine if adding dexmedetomidine to an erector spinae plane block (ESPB) that is guided by ultrasound (US) is beneficial for treating immediate postoperative pain following shoulder arthroscopy. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In the 13 trials with 430 patients in the DEX group and 393 in the control group, ESPB was performed at different levels. In one trial, it was performed at the level of the shoulder ( 37 ); in two trials, at the level of the lumbus and abdomen ( 35 , 36 ); and in 10 trials, at the level of the chest ( 7 9 , 34 , 38 43 ). The blocks provided surgical anesthesia in all 13 trials ( 7 9 , 34 43 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 13 trials with 430 patients in the DEX group and 393 in the control group, ESPB was performed at different levels. In one trial, it was performed at the level of the shoulder ( 37 ); in two trials, at the level of the lumbus and abdomen ( 35 , 36 ); and in 10 trials, at the level of the chest ( 7 9 , 34 , 38 43 ). The blocks provided surgical anesthesia in all 13 trials ( 7 9 , 34 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…The blocks provided surgical anesthesia in all 13 trials ( 7 9 , 34 43 ). All trials used long-acting LAs, including levobupivacaine in one trial ( 43 ), bupivacaine in three trials ( 37 , 40 , 41 ), and ropivacaine in nine trials ( 7 9 , 34 36 , 38 , 39 , 42 ). DEX was used at a concentration of 0.5 μg/kg in three trials ( 9 , 37 , 40 ), 1 μg/kg in nine trials ( 7 , 8 , 34 36 , 38 , 41 43 ), and both concentrations in one trial ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proper tube position was confirmed by auscultation and fiberoptic bronchoscopy. The ventilation settings during surgery were tidal volume ( 7-10 mL kg -1 (ideal body weight) ), a fraction of inspired oxygen (0.5-1.0), and end-tidal CO 2 partial pressure (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Following surgery, patients were admitted to the Intensive Care Unit (ICU).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, Agamohammid et al observed that dexmedetomidine added to bupivacaine epidural infusion provides better pain control than bupivacaine alone (22). Hamed et al showed that adding dexmedetomidine in ultrasound-guided ESPB is associated with a better analgesic effect by reducing intraoperative fentanyl and postoperative morphine consumption with a more prolonged analgesic effect and stable hemodynamics (39). Also, Song and Lu in a meta-analysis of randomized controlled trials reported that dexmedetomidine administered before anesthesia in thoracoscopic surgery can substantially improve the analgesic efficacy (40).…”
Section: Impact Of Dexmedetomidine and Dexamethasone On Postoperative...mentioning
confidence: 99%